Behaviour of moment resisting reinforced concrete frames subjected to column removal scenario. Issue 1 (March 2021) - Matrood, Methaq S.; Al-Rifaie, Ali; Zinkaah, Othman Hameed; Shubbar, Ali A.
Abstract: Researchers awarded a considerable attention to progressive collapse analysis in recent years to avoid the partial or entire failure of structures. General Service Administration guidelines (GSA) established the base to deal with such catastrophic failure. For multi-story building, these guidelines proposed column removal scenario in which one or more columns in different locations should be removed from a structure. Then, the response of entire structure with the column omitted should sustain the loading applied ensuring no global failure occurred. In this paper, three-dimensional reinforced concrete (RC) frame is constructed and analyzed using the commercial program SAP2000. Non-linear static analysis is employed to obtain Demand Capacity Ratios (DCR) for beams and the displacement of joint connecting beams to column in the selected frame. The response of moment resisting RC frame under column removal scenario is presented and discussed in terms of strength and displacements in critical locations in RC frame to evaluate the strength of such frame against progressive collapse.